COMPETENCE AND COOPERATION OF THE PUBLIC PROSECUTION OFFICE WITH THE MINISTRY OF INTERIOR OF THE REPUBLIC OF MACEDONIA - Aleksova, Sonja (Journal of process management and new technologies, 2017)
The investigation on the public prosecutors of the Republic of Macedonia and its role and responsibility as well as its cooperation with the authorities is a particular challenge which requires serious approach. The european public prosecution is still reflecting two contrasting traditions, which are adversarial and inquisition proceedings. In the middle ages, in all european countries was known the competence of individuals and their power to initiate criminal proceedings, thus it suggests that there was a system of private prosecution. The public prosecution office is a specialized and specific state institution carrying out legal measures against people who have committed crime and other offences as stipulated by law. The public prosecution office represents a special state body which is independent from the judical and executive powers.